Economies of scale in the water sector: a survey of the empirical literature - Ferro, Gustavo (2011)
The issue of the most favorable size and optimal industry structure in the water sector is a relevant topic in many countries, due to fragmentation of the water sector and the key role played by municipalities. Important debates are taking place worldwide about how to provide universal access to the water supply and offer an efficient service. Regarding efficiency, the possibility of exploiting economies of scale would imply better resource allocation, the potential for lower water charges, and greater geographical coverage. By surveying the empirical research from different parts of the world, we aim to shed some light on the topic of economies of scale, and to provide a synthesis of the literature. We also aim to determine whether there is a tradeoff between centralization and decentralization. Our survey shows that, for several countries, variations in efficiency of water provision due to economies of scale do exist. Increases in efficiency related to economies of scale are found for populations in the range of 100,000 to 1 million people served. For larger populations, volume- or density-constant returns to scale are observed, followed by decreasing returns to scale; the reverse occurs for smaller values, suggesting that cost savings are derived from consolidation of providers. [Returns to scale refer to changes in output resulting where all inputs increase by a constant factor. If output increases by that same proportional change, then there are constant returns to scale. If output increases by less than that proportional change, there are decreasing returns to scale. If output increases by more than that proportional change, there are increasing returns to scale. Returns to scale is a technological phenomenon, due to the relationship between inputs and outputs in the production function. Economies of scale refer to reductions in unit cost as the scale of production increases. Diseconomies of scale are the opposite: increasing in unit costs as the scale of production increases. Scale changes mean a proportional increase in all factors of production. Economies of scale are a economical phenomenon, due to the relationship between unit costs and the level of production.